PRAGMATIC ROLE OF SPEECH ACT COMMUNICATION AMONG NON-ENGLISH DEPARTMENT STUDENTS - Pratomo Widodo; Retma Sari (Universitas Tidar, 2023)
This paper describes about the problems in the speech act of Non-English department students especially in speaking class. Assessing the product tends to be more difficult than assessing the receptive skills namely listening and reading. The lecturer needs to pay more attention in assessing these skills, especially for non-English department students who are in the beginning level of English ability. Therefore, the aims of this research were to find out: The test format, marking criteria and the scoring scheme used by the lecturers in assessing students‘ productive skills in part of Speech Act. This study used descriptive qualitative method. Data collection techniques were carried out through observation, recording, and carried notes taking techniques. The subject of this research is the 1st-semester student of the accounting program. The data were taken from observation, interview and document analysis. The results of this research were : 1) The test formats used by the teachers to assess speaking skills were interview, picture description, and presentation. The criteria used by the teachers were pronunciation, vocabulary and fluency for speaking assessment. The lecturers use the scoring scale to score students‘ productive skills. The scale itself depends on the criteria or language components which were being assessed and each scale of score has its own description.